The Influence of Pre‐Electrospinning Plasma Treatment on Physicochemical Characteristics of PLA Nanofibers. Issue 11 (25th August 2019) - Rezaei, Fatemeh; Planckaert, Tom; Vercruysse, Chris; Verjans, Jente; Van Der Voort, Pascal; Declercq, Heidi; Hoogenboom, Richard; Morent, Rino; De Geyter, Nathalie
Abstract: Morphology, crystallinity, thermal, and mechanical properties of nanofibrous mats are known to highly affect the behavior of these materials in desired applications. In this study, multiple characteristics of poly(lactic acid) (PLA) nanofibrous mats prepared from plasma‐treated pre‐electrospinning solutions are studied as a function of various plasma operational parameters. X‐ray diffraction, differential scanning calorimetry, thermogravimetric analysis, X‐ray photoelectron spectroscopy, scanning electron microscopy, and tensile tests are performed. In addition, the pristine and plasma‐treated PLA solutions are examined with size exclusion chromatography to study the effect of the conducted pre‐electrospinning plasma treatments (PEPT) on the molecular weight of PLA. Aging analysis of the pristine and plasma‐treated solutions is also performed by evaluating the viscosity, conductivity, surface tension, and pH during an aging period of 10 days. To investigate if the results are only affected by the plasma treatment or also affected by the electrospinning, pristine and plasma‐treated PLA cast layers are also analyzed. The results reveal that PEPT preserved the surface chemical composition of the nanofibers and the molecular weight distribution of PLA, while morphology and mechanical properties of the nanofibers are considerably enhanced. Moreover, plasma‐treated polymer solutions resulted in the formation of nicely elongated nanofibers up to 4 days after plasma treatment. Abstract : Poly(lactic acid) spinning solutions in chloroform and 5, 5‐ N ‐dimethylformamide are exposed to pre‐electrospinning plasma treatment (PEPT). Physicochemical properties of the resultant PLA nanofibrous mats are carefully examined by using a wide range of analysis methods, including SEC, DSC, TGA, XRD, XPS, SEM, and mechanical testing; it is revealed that the physicochemical properties of the nanofibers are significantly enhanced after PEPT.